Statistical Modeling of Variability in Sediment-Water Nutrient and Oxygen Fluxes - Serpetti, Natalia; Witte, Ursula F. M.; Heath, Michael R. (Frontiers in Earth Science, 2016)
Mineralisation of organic detritus in the marine surficial sediments generates a flux of dissolved inorganic nutrient between the sediment and overlying water column. This is a key process in the marine ecosystem, which links the food webs of the sea-floor and the overlying water-column, and is potentially affected by a range of interacting environmental and sedimentary factors. Here, we use General Additive Models (GAM) to statistically disentangle some of the factors controlling the seasonal and spatial variability in nutrients and oxygen fluxes in a field dataset collected in the North Sea off the northeast coast of Scotland. We show that sediment grain size, turbidity due to sediment re-suspension, temperature, and sediment chlorophyll content were the key factors affecting oxygen, ammonia, and silicate fluxes. However, phosphate fluxes were only related to suspended sediment concentrations, whilst nitrate fluxes showed no clear relationship to any of the expected drivers of change, probably due to the effects of denitrification. Our analyses show that the stoichiometry of nutrient regeneration in the ecosystem is not necessarily constant and may be affected by combinations of processes.